DIRECT AND DERIVATIVE SPECTROPHOTOMETRIC DETERMINATION OF CADMIUM (II) IN PRESENCE OF MICELLAR MEDIUM IN BIOLOGICAL MATERIALS AND IN ALLOY SAMPLES USING CINNAMALDEHYDE-4- HYDROXY BENZOYLHYDRAZONE (CMHBH) - D.GOPALA KRISHNA; N.DEVANNA; K.B.CHANDRASEKHAR (International Journal of Pharma and Bio Sciences, 2010)
A rapid, simple, sensitive and selective spectrophotometric method has been developed for the determination of Cadmium (II) using newly synthesized reagent cinnamaldehyde-4- hydroxybenzoylhydrazone (CMHBH) in neutral surfactant of TritonX-100-5% (micellar medium). Cadmium (II) forms a yellow coluored water-soluble complex with Cinnamaldehyde-4-hydroxy benzoylhydrazone in the pH range 8.0-9.0. The complex shows maximum absorbance at lmax 383 nm and in the pH range 8.0-9.0. However, at this wavelength, the reagent shows considerable absorbance. At lmax 383 nm, the complex shows maximum absorbance while the reagent blank shows negligible absorbance. Hence, analytical studies are carried out at lmax 383 nm and at pH 9.0 (Phosphate buffer) against reagent blank. Beer’s law is obeyed in the range 0.056-0.562 μg ml-1 and the optimum concentration range from ringbom plot is 0.112-0.505 mg/ml of Cadmium (II). The molar absorptivity and Sandell’s sensitivity for the coloured solution are found to be 5.6 x 104 L mol-1 cm-1 and 0.002-μg. cm-2 respectively. The interference effect of various diverse ions has been studied. The complex shows 1:1 [Cd (II): CMHBH] stoichiometry with stability constant 12.63 x 106. The standard deviation of the method in the determination of 0.224-μg ml-1 of Cadmium (II) is 0.0101 and the Relative standard deviation is 1.13%. First and second order derivative spectroscopic method is developed at lmax 450 nm and 470 nm respectively for the determination of Cadmium (II), which is more sensitive than the zero order method. The developed method has been employed for the determination of Cadmium (II) in biological materials (Cigarette tobacco, Radish flesh and Cabbage) and in alloy samples. The results are in good agreement with the certified values.